2022
DOI: 10.36565/jab.v11i1.448
|View full text |Cite
|
Sign up to set email alerts
|

Pola Menyusui Ibu Postpartum di Praktek Mandiri Bidan

Abstract: Infant morbidity rate is the second indicator in determining the health status of children because it reflects the baby's weak immune system. This is influenced by nutritional factors, socio-economic factors and demographics. Breastfeeding is related to the fulfillment of infant nutrition. Almost all infants in Indonesia (96%) have received breast milk, but infant mortality and morbidity rates are still high. It is still found in the fact that there is a tendency for postpartum mothers to discard some of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Previous research showed that 96.3% of postpartum mothers gave only breast milk without other food and drink until the age of 40 days. (Nurita, 2022) Exclusive breastfeeding means not giving the baby food and drink other than breast milk until the baby is 6 months old, except for medicines and vitamins. (WHO, 2020) It can be assumed that babies are only given breast milk, without additional liquids such as formula milk, oranges, tea water, water, and without additional solid foods, for example bananas, papaya, milk porridge, biscuits, rice porridge, or other food.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that 96.3% of postpartum mothers gave only breast milk without other food and drink until the age of 40 days. (Nurita, 2022) Exclusive breastfeeding means not giving the baby food and drink other than breast milk until the baby is 6 months old, except for medicines and vitamins. (WHO, 2020) It can be assumed that babies are only given breast milk, without additional liquids such as formula milk, oranges, tea water, water, and without additional solid foods, for example bananas, papaya, milk porridge, biscuits, rice porridge, or other food.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini sejalan dengan teori Notoadmojo (2010) bahwa salah satu faktor yang mempengaruhi pengetahuan adalah pendidikan. 7 Pengetahuan tentang ASI didapatkan dari informasi yang berasal dari hasil membaca, mendapat informasi dari orang lain. Dalam hal ini ibu yang mendapatkan informasi tentang pangan lokal yang dapat meningkatkan produksi ASI dapat merubah sikap ibu yang akhirnya merubah perilaku ibu tersebut.…”
Section: Hasil Dan Pembahasanunclassified
“…Dalam hal ini ibu yang mendapatkan informasi tentang pangan lokal yang dapat meningkatkan produksi ASI dapat merubah sikap ibu yang akhirnya merubah perilaku ibu tersebut. 7 Berdasarkan hasil analisis data kuesioner sikap pre-test dan post-test dari 10 orang peserta didapatkan hasil sebagai berikut: Berdasarkan tabel 2 dapat dilihat terjadi peningkatan sikap peserta kegiatan dilihat dari beda/selisih hasil pre-test dan post-test. Kuesioner sikap pre dan post test berisi 10 butir pernyataan sikap yang memuat pernyataan terkait manfaat pangan lokal untuk peningkatan produksi ASI pada ibu menyusui.…”
Section: Hasil Dan Pembahasanunclassified